Vaginal Microbiomes Associated With Aerobic Vaginitis and Bacterial Vaginosis - Evelyn Kaambo; Evelyn Kaambo; Evelyn Kaambo; Charlene Africa; Ramadhani Chambuso; Ramadhani Chambuso; Jo-Ann Shelley Passmore; Jo-Ann Shelley Passmore; Jo-Ann Shelley Passmore (Frontiers Media S.A., 2018)
A healthy vaginal microbiota is considered to be significant for maintaining vaginal health and preventing infections. However, certain vaginal bacterial commensal species serve an important first line of defense of the body. Any disruption of this microbial barrier might result in a number of urogenital conditions including aerobic vaginitis (AV) and bacterial vaginosis (BV). The health of the vagina is closely associated with inhabitant microbiota. Furthermore, these microbes maintain a low vaginal pH, prevent the acquisition of pathogens, stimulate or moderate the local innate immune system, and further protect against complications during pregnancies. Therefore, this review will focus on vaginal microbial "health" in the lower reproductive tract of women and on the physiological characteristics that determine the well-being of reproductive health. In addition, we explore the distinct versus shared characteristics of BV and AV, which are commonly associated with increased risk for preterm delivery.